Comparison of Supreme Court and Constitutional Court Decisions Based on Legal Standing in Open Legal Policy Pilkada 2024 - Salsa Octaviani S; Mulyadi, Dedi; Permana, Ajeng; Asriani, Fina; Salman Fikry, M. Dika; Hidayat, Zulfikar Nugraha (Pubmedia Social Sciences and Humanities, 2025)
This journal abstract focuses on a comparative analysis between the decisions of the Supreme Court (MA) and the Constitutional Court (MK) in the context of legal standing in the 2024 Pilkada open legal policy. This research aims to identify differences in the interpretation and application of the law by the two institutions regarding the legal standing of the applicant. The research method used is a mixed method of quantitative and qualitative. The quantitative approach is used to collect numerical data on the number and characteristics of cases, while the qualitative approach is applied to analyse the legal context and arguments used by the Supreme Court and Constitutional Court in deciding cases. The results show that the Supreme Court has a tendency to tighten legal access by focusing on procedural aspects, while the Constitutional Court provides wider space for public participation in assessing regulatory justice. This difference in approach results in potential conflicts that can affect the stability of Pilkada regulations. This research is expected to provide a new perspective for policymakers in formulating clearer and more consistent regulations, while increasing the transparency of decision-making in the judiciary.